Reading and Writing: Advances and Perspectives for the 15th Anniversary of the Revista de Investigación en Logopedia - Suárez-Coalla, Paz (Revista de Investigación en Logopedia, 2025)
This special issue, published to commemorate the 15th anniversary of the Revista de Investigación en Logopedia, dedicated to the study of reading and writing acquisition and processing—complex processes involving the interaction of linguistic, cognitive, metacognitive, and affective skills. It brings together fifteen papers that, from an integrative perspective, examine the various factors involved in reading and writing, with special attention to diverse populations such as students with dyslexia, developmental language disorder, cochlear implant users, and bilingual speakers. The studies address key dimensions such as orthographic systems, visual perception, prosody, morphology, executive functions, reading comprehension, and emotional language processing. In addition to their theoretical and empirical relevance, the articles provide practical implications for assessment and speech-language intervention. This commemorative volume not only celebrates fifteen years of research, but also reaffirms the journal’s commitment to integrating research-based knowledge into clinical and educational practice.
Keywords: Assessment and intervention; Cognitive-linguistic-affective processes; Individual diversity; Reading; Writing